498 It Makes Relationships Harder: The Role of Narcolepsy in Social and Romantic Relationships in Young Adults. (3rd May 2021) - Davidson, Ryan; Biddle, Kelsey; Scammell, Thomas; Nassan, Malik; Zhou, Eric
Abstract: Introduction: Narcolepsy typically begins during adolescence/young adulthood – a crucial period for developing relationships. As symptoms would be expected to impact social interactions, we studied how narcolepsy impacts social, romantic, and sexual relationships in young adults. Methods: Young adults (18–39 years; N=262) with a self-confirmed narcolepsy diagnosis were recruited through national narcolepsy patient organizations. Participants completed an online survey, including open-ended questions, to evaluate their social, romantic, and sexual relationships and communication with medical providers. Results: Participants (mean=28.5 years old; SD=5.6) were primarily female (87%), White/Caucasian (92%), employed (75%), and had Narcolepsy Type I (56%). All participants indicated that narcolepsy made social life or entering relationships somewhat or a lot more difficult. Rates of cohabitation and marriage were comparable to nationally representative samples. On the Couples Satisfaction Index, most participants reported feeling satisfied with their romantic relationships (mean=15.8; SD=4.3). On the Multidimensional Scale of Perceived Social Support, participants reported receiving greater support from their significant others (mean=4.5; SD=1.4) compared to both family (mean=3.7; SD=1.5; p<.05) and friends (mean=3.9; SD=1.4; p<.05). There was no difference between family and friends (p>.05). Eighty-percent of participants indicated that narcolepsy impacted their sex life, including experiencing cataplexy or falling asleep during sex. Few participants indicated that their providers asked about their social (31%) and sex life (10%). In contrast, 73% of participants wanted providers to ask about social life and 45% wanted providers to ask about sex life. Conclusion: Narcolepsy substantially impacts social functioning in young adults. They often prioritize the development of a single, meaningful romantic relationship as their disorder makes sustaining more social relationships challenging ("I do not go out and socialize at all, but spend all my time at home nurturing my romantic relationship because it's the most important to me"). At a time of sexual development, there are considerable implications of narcolepsy symptoms on their sexual experiences. Though many participants were interested in discussing their social, romantic, and sexual relationships with medical providers, only a small proportion of providers inquire. Effective treatment of narcolepsy in young adults should include support for the impact of the disorder on relationship health. Support (if any): Jazz Pharmaceuticals.